IN VITRO TEST OF MANNOSE SPECIFIC ADHESIN (MSA) OF LACTOBACILLUS SP. AND ETHANOL EXTRACT OF SKIN FRUIT GARCINIA MANGOSTANA L. BY USING SACCHAROMYCES CEREVISIAE - Yulinery., dkk, T. (BPPT)
Infection disease is a threat for human life. Research on preventing infection disease is very important. The aim this research was to improve the preventing of infection disease. This research was the basic on identification of MSA activity. The in vitro result of MSA which was isolated from mangosteen (Garcinia mangostana L.) and the extract of the fruit skin byusing Saccharomyces cerevisiae. The result showed that there were 11 isolates of potential Lactobacillus, that have variation in MSA activities. Four isolates of them showed that the higher activities between 9.6-11.8 were TM1, BST1, BST2, and BST5. The MSA activities showed by reducing coagulation after adding D-Mannose. The highest activities showedby isolate TM1, and the lowest showed by isolate BST7. By using this method it is clearly found that the skin fruit not contain MSAkeywords : mannose-specific adhesin (msa ), probiotic, Saccharomyces cerevisiae.